PRINCIPALâS SUPPORT, TEACHERS OF PHYSICAL, SPORT, HEALTH EDUCATION AND PARENTS INTEREST TO THE FOLLOWING OF STUDENTS BADMINTON EXTRACURRICULAR AT SMAN 1 BABAT oleh Mohammad Ali Fauzi Yonny Herdyanto, S.Pd.,M.Kes. (Arena, 2012)
ABSTRACT           School is a place to study and gain useful experience for his future. In order for effective teaching and learning process so that it is necessary to achieve educational goals of planning. Extracurricular is a form of activities outside the curriculum as a channel of talent or aspirations of the students themselves, there are arts activities or sports at school, which for this activity has two elements. The element activity is a part of an effort and the human element which is fun to move through the physical, mental and emotional. So, extracurricular activities will have a positive influence for people who do that, because of the extracurricular activities students can develop their talent  appropriate with an interest in the arts and sport.            The using research includes the type of qualitative research because it shows more to the establishment of substantive theory based on concepts arising from empirical data. The process of data retrieval performed using an interview involves a source. Sources of data from the study is from the Principal of SMAN 1 Babat, teachers of physical, sport, healthy education, parents of students who join the extracurricular activities, and students of SMAN 1 Babat who follow the badminton extracurricular. The research was conducted in March at SMAN 1 Babat.           The results about the supports of the principals, teachers of physical, sport, health education and parents to the students’ interest in the badminton extracurricular at SMAN 1 Babat is that although it has not been focused on badminton extracurricular activities, head of SMAN 1 Babat continued to support all existing activities, teachers of physical, sport, health education support it in the form motivate students to follow the badminton extracurricular activities at SMAN 1 Babat, they encourage all the students to practice. Support from parents is given in the form of advice to their children, giving all the necessary requirements for the badminton  extracurricular and  provid  nutrition to support the exercise.   Keywords: support, student interest, motivation, extracurricular, badminton